Audio-Visual Causality and Stimulus Reliability Affect Audio-Visual Synchrony Perception - Li, Shao; Ding, Qi; Yuan, Yichen; Yue, Zhenzhu (Frontiers in Psychology, 2021)
People can discriminate the synchronization between audio-visual scenes. However, the sensitivity of audio-visual synchrony perception can be affected by many factors. By adopting a simultaneity judgment task, the present study investigated whether the synchrony perception of complex audio-visual stimuli was affected by audio-visual causality and stimulus reliability. In Experiment 1, the results showed that audio-visual causality could increase the sensitivity to audio-visual onset asynchrony (AVOA) of both action stimuli and speech stimuli. Moreover, participants were more tolerant of AVOA of speech stimuli than that of action stimuli under high causality, while no significant difference between these two kinds of stimuli was found under low causality. In Experiment 2, the speech stimuli were manipulated with either high or low stimulus reliability. The results revealed a significant interaction between audio-visual causality and stimulus reliability. Under low causality condition, the percentage of “Synchronous” responses of audio-visual intact stimuli was significantly higher than that of visual_intact/auditory_blurred stimuli and audio-visual blurred stimuli. By contrast, no significant difference among all levels of stimulus reliability was observed under high causality condition. Our study supported that there existed a synergistic effect of top-down processing and bottom-up processing in audio-visual synchrony perception.